Day/night expression of MT1 and MT2 receptors in hypothalamic nuclei of the primate Sapajus apella - Pinato, Luciana [UNESP]; Ramos, Dayane; Hataka, Alessandre [UNESP]; Rossignoli, Patricia S. [UNESP]; Granado, Marcos Donisete; Mazzetto, Marina Cardoso; Campos, Leila M.G. [UNESP] (Elsevier, 2017)
Melatonin is involved in the temporal organization of several physiological and behavioral events, controlled by hypothalamic nuclei, like sleep, feeding, reproduction and metabolic modulation and acts through two types of high-affinity G protein-coupled membrane receptors: MT1 and MT2. This study aimed to investigate the expression of MT1 and MT2 receptors proteins in four hypothalamic nuclei, i.e., SCN, supraoptic (SON), paraventricular (PVN) and anteroventral periventricular nuclei (AVPV), of the diurnal primate Sapajus apella using immunohistochemistry. Since these areas are involved in the expression of biological rhythms, they are candidates to have variations in their neurochemistry, so the MT1 and MT2 expression has been analyzed at a point in light and another in the dark phase. Both receptors were found to have day/night differences in the four hypothalamic nuclei with an apparent inverse expression in the SCN compared with the other areas. These differences could be related to the idea that the individual should be prepared to respond by different ways to melatonin signal within the several processes and can contribute to the efficacy of melatonin ligands or melatonin in therapies.
Keywords: Behavior; Biological rhythms; Hypothalamus; Melatonin